From the Outskirts to the Beats: The Sonic Revolution of DJ Marfox and DJs Di Guetto - Mineiro, João. (CRIA Working Papers, 2025)
On September 18, 2006, a group of young DJs and producers from the outskirts of Lisbon released DJ’s do Guetto Vol. 1, a compilation of 37 tracks blending the musical legacies of kuduro, tarraxo, and funaná with global Black and Afrodiasporic sounds, primarily from house and techno. Created by DJs Marfox, Pausas, N.K., Jesse, Fofuxo, and Firmeza, the album synchronized a set of historical, cultural, and urban coordinates, synthesizing the desire to create a sound that reflected their own experiences, imaginaries, and social worlds. This text argues that, by embracing the idea that anyone can produce music, these producers subverted the prevailing rules of the music field, which had been based on a professional monopoly legitimized by virtuosity. It further contends that this gesture expanded music’s role as a space of cultural and political affirmation for young Afro-descendant and Black Portuguese generations, opening horizons of expectation that had been systemically constrained. Such an opening generated a musical repertoire that disrupted lusotropicalist narratives embedded in contemporary Portuguese culture, asserting music as a powerful medium of self-representation for the Black community in Portugal. This is a revised version of a presentation delivered at the “Second IN2PAST Field Trip” on December 12, 2024 — a listening session dedicated to music as an object of research. On that occasion, I proposed a collective listening of “Drift Furioso” by DJ Marfox, one of the tracks featured on DJ’s do Guetto Vol. 1, which served as the starting point for this reflection.